2015
DOI: 10.1111/nph.13280
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific FLAGELLINSENSING 2 (FLS2) expression in roots restores immune responses in Arabidopsis fls2 mutants

Abstract: SummaryThe flagellin receptor of Arabidopsis, At-FLAGELLIN SENSING 2 (FLS2), has become a model for mechanistic and functional studies on plant immune receptors. Responses to flagellin or its active epitope flagellin 22 (flg22) have been extensively studied in Arabidopsis leaves. However, the perception of microbe-associated molecular patterns (MAMPs) and the immune responses in roots are poorly understood.Here, we show that isolated root tissue is able to induce pattern-triggered immunity (PTI) responses upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 48 publications
(76 reference statements)
8
71
1
Order By: Relevance
“…Detection of SCMV in the samples was performed using an antiserum specific for SCMV CP with a secondary antibody conjugated to alkaline phosphatase with phosphatase activity detected using nitroblue tetrazolium/5‐bromo‐4‐chloro‐3‐indolylphosphate (NBT/BCIP) (Roche) (Xia et al ., ). Quantification of CP was estimated using ImageJ software (http://imagej.net/) as described by Wyrsch et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Detection of SCMV in the samples was performed using an antiserum specific for SCMV CP with a secondary antibody conjugated to alkaline phosphatase with phosphatase activity detected using nitroblue tetrazolium/5‐bromo‐4‐chloro‐3‐indolylphosphate (NBT/BCIP) (Roche) (Xia et al ., ). Quantification of CP was estimated using ImageJ software (http://imagej.net/) as described by Wyrsch et al ().…”
Section: Methodsmentioning
confidence: 99%
“…We therefore focused on the response at 2 h post elicitor treatment to capture the initial primary differences between flg22 and Pep1-triggered immunity pathways, prior to secondary activation of cross-talking networks and later PTI responses such as development and growth-related gene networks as a result of PTI-induced growth inhibition (observed at 4 d post elictor treatment. In addition, previous studies have demonstrated PEPR1/2 and FLS2 protein abundance in these cell types and the fast movement of flg22 and Pep1 reaching pericycle cells within a few minutes (Wyrsch et al, 2015; Ortiz-Morea et al, 2016).…”
Section: Resultsmentioning
confidence: 81%
“…Representing the interface with the soil environment, the epidermis and cortex are expected to be crucial for root protection against pathogen invasion. As pericycle cells, the outermost cell layer of the inner root tissue, guard the vasculature and were recently shown to be highly responsive to immune elicitors (Wyrsch et al, 2015). Therefore, pericycle, epidermis and cortex cells were selected for our transcriptional analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations